Conductive silver paste and preparation method thereof and N-type TOPCon solar cell
By using a specific composition of conductive silver paste in N-type TOPCon solar cells, the silver paste adaptation problem in the LECO process is solved, and the good contact between the four secondary gates and the silicon wafer is achieved, improving the photoelectric conversion efficiency and battery performance.
Patent Information
- Application Number
- CN202411151490.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-21
AI Technical Summary
In the prior art, the LECO process lacks the adapted silver paste when preparing the four secondary gates of the N-type TOPCon solar cell, which makes it difficult for the passivation layer to form good contact, severe erosion, and affects the battery performance.
Provide a conductive silver paste, containing silver powder, glass powder and organic carrier, through a specific proportion of composition and preparation method, to form silver paste suitable for LECO sintering, and is used to prepare four sub-gate of N-type TOPCon solar cells to reduce the sintering temperature. and passivation layer erosion.
The good silver-silicon ohmic contact between the four secondary gates and the silicon wafer is achieved, which improves the photoelectric conversion efficiency and carrier transmission capability, reduces the passivation layer erosion loss, and improves the overall performance of the battery.
Smart Images

Figure CN118658653B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive materials and relates to a conductive silver paste and a preparation method thereof and an N-type TOPCon solar cell. Background Art
[0002] As a key new clean energy source, solar cells have achieved rapid development in recent years. Solar cell production efficiencies exceeding 26% have reached a peak. Currently, the most popular mainstream N-type cells in the photovoltaic industry are TOPCon (Tunnel Oxide Passivated Contact) cells and HJT (Heterojunction with Intrinsic Thin-film). Both are considered the most promising next-generation solar cell technologies in the past two years. HJT offers high mass production efficiency and a clear cost reduction path, making it a promising long-term technology. N-type TOPCon solar cells, with their high ultimate efficiency and low production line modification costs, have become the trend in recent years. N-type TOPCon solar cells use N-type silicon as a substrate material and enhance backplane reflectivity by adding oxides to improve photoelectric conversion efficiency. The process is straightforward: it adds a tunnel oxide layer to the backplane of the existing PERC (Passivated Emitter and Rear Cell) cell, further enhancing light reflection and absorption. N-type TOPCon solar cells have obvious advantages, including high photoelectric conversion efficiency, high investment cost-effectiveness, and excellent power generation performance.
[0003] To further improve cell photovoltaic conversion efficiency, the LECO (Laser-enhanced contact optimization) process is increasingly being used in the market to fabricate N-type TOPCon solar cells, replacing traditional sintering techniques. During traditional silver paste sintering, the conductive silver paste comes into direct contact with silicon, forming a silver-silicon alloy interface. This inevitably erodes the passivation layer and requires relatively high sintering temperatures. Since the maximum sintering temperature exceeds 800°C, this damages the cell, reducing open-circuit voltage and overall efficiency. Using the LECO process as a post-sintering treatment mitigates passivation layer erosion and lowers contact sintering temperatures, thereby achieving higher open-circuit voltage and fill factor values in industrial N-type TOPCon solar cells. Traditional sintering technology is a one-step process, but the addition of LECO sintering transforms it into a two-step process. This not only improves the average performance of solar cells but also allows for fine-tuning of individual processes, successfully separating the erosion of the passivation layer and the formation of the silver-silicon alloy contact during sintering. This allows for precise control of passivation layer erosion and a more uniform contact resistivity, resulting in a narrower fill factor distribution and a 0.3% to 0.6% increase in photoelectric conversion efficiency. However, the LECO process is still in its initial application stages, and developing a compatible electronic paste is crucial for achieving large-scale application. Traditional PERC cell pastes are highly corrosive, making them difficult to apply to LECO sintering. The most pressing need for N-type TOPCon solar cells is to formulate a suitable low-corrosion silver paste that can form a good ohmic contact at the interface and reduce erosion of the passivation layer. Summary of the Invention
[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a conductive silver paste and a preparation method thereof and an N-type TOPCon solar cell, so as to solve the problem in the prior art that when the LECO process is used to prepare the four sub-grids of the N-type TOPCon solar cell, there is a lack of adapted silver paste, and the four sub-grids are difficult to form good contact with the passivation layer.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A first aspect of the present invention provides a conductive silver paste, wherein the raw materials of the conductive silver paste include, by mass fraction: 88.2% to 89.0% silver powder, 1.5% to 2.3% glass powder, and 9.5% organic vehicle;
[0007] The glass powder comprises, by mass fraction, 57.5% to 59.5% lead oxide, 19.8% to 23% boron trioxide, 7.4% to 9.4% silicon dioxide, 1.8% to 6% aluminum trioxide, 1% to 3% zinc oxide, 1% to 4% diammonium hydrogen phosphate, 0% to 1.5% potassium carbonate, 0% to 3.8% sodium carbonate, and 0% to 2.3% lithium carbonate.
[0008] The organic carrier is composed of organic carrier A, organic carrier B and organic carrier C;
[0009] The organic carrier A is composed of acrylic resin, hexadecyl alcohol ester and butyl carbitol acetate;
[0010] The organic carrier B is composed of ethyl cellulose, polyvinyl butyral, butyl carbitol acetate, hexadecyl alcohol ester and dimethyl adipate;
[0011] The organic carrier C consists of formamidine sulfinic acid, polyamide wax, butyl carbitol acetate, hexadecyl alcohol ester and dimethyl adipate.
[0012] The conductive silver paste is used for preparing four sub-grids of an N-type TOPCon solar cell through LECO sintering.
[0013] Preferably, in the 9.5% organic vehicle, the content of organic vehicle A is 4% to 6.4%, the content of organic vehicle B is 3% to 5.4%, and the content of organic vehicle C is 0.1%.
[0014] Preferably, the organic vehicle A comprises, by mass fraction, 17% to 23% of acrylic resin, 35% to 46.7% of hexadecyl alcohol ester, and 33.7% to 45% of butyl carbitol acetate.
[0015] Preferably, the organic carrier B is composed of, by mass fraction, 4.3% to 5.8% of ethyl cellulose, 12.8% to 17.3% of polyvinyl butyral, 62.6% to 70% of butyl carbitol acetate, 5.3% to 10.7% of hexadecyl alcohol ester and 4.7% to 9.3% of dimethyl adipate.
[0016] Preferably, the composition of the organic carrier C is, by mass fraction, 7% to 13% of formamidine sulfinic acid, 9.7% to 10.3% of polyamide wax, 19.3% to 20.7% of butyl carbitol acetate, 33.8% to 36.2% of hexadecyl alcohol ester and 24.2% to 25.8% of dimethyl adipate.
[0017] The second aspect of the present invention provides a method for preparing the above-mentioned conductive silver paste, wherein the preparation process comprises: stirring and mixing an organic vehicle, glass powder and silver powder, grinding and filtering to obtain the conductive silver paste;
[0018] The preparation process of the glass powder is as follows: lead oxide, boron trioxide, silicon dioxide, aluminum trioxide, zinc oxide, diammonium hydrogen phosphate, potassium carbonate, sodium carbonate and lithium carbonate are mixed and melted, and then quenched to obtain glass fragments, the glass fragments are ball-milled to obtain glass slurry, and the glass slurry is sieved and dried to obtain glass powder;
[0019] The preparation process of the organic carrier is as follows: preparing organic carrier A, organic carrier B and organic carrier C by mixing and stirring respectively, and obtaining an organic carrier by mixing and stirring the three organic carriers and heating them.
[0020] Preferably, the heating temperature after mixing the three organic carriers is 60° C. to 70° C., and the stirring time is 1 h to 2 h.
[0021] The third aspect of the present invention provides an N-type TOPCon solar cell, wherein the four sub-grids of the N-type TOPCon solar cell are prepared by the above-mentioned conductive silver paste. The preparation process is: the conductive silver paste is printed on the four sub-grid positions of the solar silicon wafer, and after printing, a single sintering is first performed, and after the single sintering, LECO sintering is performed to finally obtain the N-type TOPCon solar cell.
[0022] Preferably, the printing speed is 400 mm / s to 500 mm / s;
[0023] Preferably, the primary sintering temperature is 740°C to 780°C, and the primary sintering time is 1.0s to 1.5s;
[0024] The sintering time of LECO is 0.7s~0.9s.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention discloses a conductive silver paste for preparing four sub-grids for an N-type TOPCon solar cell. The raw materials include silver powder, glass powder, and an organic vehicle. The weight percentages of the components are as follows: 88.2% to 89.0% silver powder, 1.5% to 2.3% glass powder, and 9.5% organic vehicle. The glass powder comprises the following components by weight: 57.5% to 59.5% lead oxide, 19.8% to 23% boron trioxide, 7.4% to 9.4% silicon dioxide, 1.8% to 6% aluminum trioxide, 1% to 3% zinc oxide, 1% to 4% diammonium hydrogen phosphate, 0% to 1.5% potassium carbonate, 0% to 3.8% sodium carbonate, and 0% to 2.3% lithium carbonate. By regulating the composition of the glass powder, the conductive silver paste can match the silver powder and the organic carrier, meeting the needs of the subsequent conductive silver paste when sintered into four sub-grids. The formed four sub-grids can form good silver-silicon ohmic contact with the silicon wafer, reduce the contact resistance of the crystalline silicon solar cell, and improve the carrier transmission capacity of the four sub-grids. The loss during the transmission process is low, and the erosion of the passivation layer on the surface of the silicon wafer can be reduced during the sintering process.
[0027] The present invention also discloses an N-type TOPCon solar cell prepared based on the above-mentioned conductive silver paste. The N-type TOPCon solar cell prepared using the above-mentioned conductive silver paste has a photoelectric conversion efficiency of up to 26.72%, and a photoelectric conversion efficiency attenuation rate of less than 20% during the acetic acid vapor resistance test, which meets the needs of N-type TOPCon solar cells and has good market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a SEM (Scanning Electron Microscope) image of the silver-silicon interface mechanically broken apart in Example 27 of the present invention;
[0029] Figure 2 is a SEM image of the silver-silicon interface milled by xenon plasma in Example 27 of the present invention;
[0030] Figure 3 This is a DSC (Differential Scanning Calorimetry) graph of the glass powder in Example 27 of the present invention. DETAILED DESCRIPTION
[0031] The structure of an N-type TOPCon solar cell consists of, from top to bottom, a front-side Ag gate, a SiN anti-reflection film, an Al2O3 passivation glass, a P-type boron diffusion layer, an N-type single crystal substrate, an SiO2 ultra-thin tunneling oxide film, a highly doped N-type polysilicon layer, a SiN anti-reflection film, and a back-side silver gate. Compared to PERC cells, N-type TOPCon solar cells use an N-type substrate and introduce an SiO2 ultra-thin tunneling oxide film. The N-type substrate effectively avoids the inherent disadvantage of high light-induced degradation of P-type cells. At the same time, the Al2O3 passivation glass and SiO2 ultra-thin tunneling oxide film further passivate the interface and reduce carrier recombination losses. Therefore, compared to PERC cells, N-type TOPCon solar cells also have a higher theoretical photoelectric conversion efficiency.
[0032] The common N-type TOPCon solar cell size on the market is 182mm×182mm×0.13mm. Due to the differences in the front and back structures of the cell, different pastes are required. The process involves first printing the conductive silver paste for the back main grid, defined as one main grid; then printing the conductive silver paste for the back sub-grid, defined as two back sub-grids; then printing the conductive silver paste for the front main grid, defined as three main grids; and finally printing the conductive silver paste for the front sub-grid, defined as four sub-grids. The conductive silver paste described in this invention only applies to the conductive silver paste for four sub-grids.
[0033] The first aspect of the present invention discloses a conductive silver paste suitable for N-type TOPCon solar cells; the raw materials of the conductive silver paste include silver powder, glass powder and an organic carrier. The mass percentage of each component is: 88.2% to 89.0% silver powder, 1.5% to 2.3% glass powder and 9.5% organic carrier. The silver powder involved in the present invention is all pure silver powder.
[0034] Among them, the glass powder includes the following components in terms of mass fraction: 57.5%~59.5% lead oxide, 19.8%~23% boron trioxide, 7.4%~9.4% silicon dioxide, 1.8%~6% aluminum trioxide, 1%~3% zinc oxide, 1%~4% diammonium hydrogen phosphate, 0%~1.5% potassium carbonate, 0%~3.8% sodium carbonate and 0%~2.3% lithium carbonate.
[0035] Among them, the total amount of organic carrier in the conductive silver paste is 9.5%, which specifically includes the following components by mass fraction: 4%~6.4% organic carrier A, 3%~5.4% organic carrier B and 0.1% organic carrier C.
[0036] The weight percentages of the components of Organic Vehicle A are: 17%-23% acrylic resin, 35%-46.7% hexadecyl alcohol ester, and 33.7%-45% butyl carbitol acetate. The weight percentages of the components of Organic Vehicle B are: 4.3%-5.8% ethyl cellulose, 12.8%-17.3% polyvinyl butyral, 62.6%-70% butyl carbitol acetate, 5.3%-10.7% hexadecyl alcohol ester, and 4.7%-9.3% dimethyl adipate. The weight percentages of the components of Organic Vehicle C are: 7%-13% formamidinesulfinic acid, 9.7%-10.3% polyamide wax, 19.3%-20.7% butyl carbitol acetate, 33.8%-36.2% hexadecyl alcohol ester, and 24.2%-25.8% dimethyl adipate.
[0037] It should be noted that organic vehicle A serves as the backbone of the organic vehicle. After the conductive silver paste is formed, the acrylic resin in organic vehicle A has a relatively large molecular weight, which allows the conductive silver paste to have a good shaping effect during printing, allowing it to stand upright and avoid collapse. The ethyl cellulose and polyvinyl butyral in organic vehicle B have relatively small molecular weights and can disperse organic vehicle A. Organic vehicle C mainly disperses silver powder and glass powder, while forming bridges between organic vehicle A and silver powder, organic vehicle A and glass powder, organic vehicle B and silver powder, and organic vehicle B and glass powder, forming a uniform silver paste across the entire formula.
[0038] A second aspect of the present invention discloses a method for preparing a conductive silver paste suitable for an N-type TOPCon solar cell, comprising the following steps:
[0039] Step 1: Mix lead oxide, boron trioxide, silicon dioxide, aluminum trioxide, zinc oxide, diammonium hydrogen phosphate, potassium carbonate, sodium carbonate, and lithium carbonate and melt them according to the above-mentioned mass ratio, quench them in water to obtain glass fragments, ball-mill the glass fragments to obtain glass slurry, and sieve and dry the glass slurry to obtain glass powder.
[0040] Preferably, the melting temperature is 1250° C. to 1350° C., and the melting time is 0.5 h to 1 h.
[0041] Step 2: prepare three organic carriers according to the above formulas of organic carrier A, organic carrier B and organic carrier C respectively, mix the three prepared organic carriers, heat and stir at 60° C. to 70° C. for 1 h to 2 h to form an organic carrier.
[0042] Step 3: After mixing silver powder, glass powder and organic carrier according to the above formula, stir in a double planetary mixer, then grind by three rollers 6 to 8 times, and filter through a 400-mesh mesh to obtain a conductive silver paste.
[0043] The third aspect of the present invention discloses an N-type TOPCon solar cell. The conductive silver paste prepared above is printed on four secondary grids of a solar silicon wafer. The conductive silver paste for the main grid, two back grids, and three main grids used in the test is verified by Hongxing paste. After printing, the corresponding pastes for the main grid, two back grids, and three main grids are dried at 200°C for 5s to 10s. Finally, the four secondary grid pastes are printed, followed by drying, primary sintering, and light injection. The above four processes are all completed in a Suzhou Maxwell single-channel system with a printing speed of 400mm / s to 500mm / s, a primary sintering time of 1.0s to 1.5s, and a peak temperature of 740°C to 780°C. LECO sintering is then performed on a Deer laser device to form an N-type TOPCon solar cell. The LECO sintering process involves scanning a 0.2mm wide laser beam across the silicon wafer, with a dwell time of approximately 0.8s on each secondary grid line, and a LECO sintering time of 0.7s to 0.9s.
[0044] The test process of the above-mentioned N-type TOPCon solar cell is as follows:
[0045] Step 1: Perform EL testing (electroluminescence testing) on the above-mentioned cells using a Suzhou Kepai EL (electroluminescence test) tester, and perform IV testing (current-voltage characteristic curve testing) using a German HALM (abbreviation of German HALM elektronik gmbh) system, and record the photoelectric conversion efficiency, opening voltage, fill and short-circuit current data.
[0046] In step 2, the silver-silicon bonding surface of the cells with high photoelectric conversion efficiency was milled using a TESCAN xenon plasma FIB-SEM (Focused Ion Beam Scanning Electron Microscope) to record the bonding state. The cells with high photoelectric conversion efficiency were then subjected to an acetic acid vapor resistance test, followed by EL and IV testing, and the photoelectric conversion efficiency decay rate was calculated. The acetic acid vapor resistance test conditions were: a saturated potassium chlorate solution with a mass fraction of 2%, a temperature of 80°C to 90°C, and a duration of 14 to 16 hours.
[0047] The following is further described with reference to specific embodiments.
[0048] Example
[0049] (A) Preparation of glass powder
[0050] The raw material mixture was mixed according to the mass ratios in Table 1 below. After melting at 1300°C for 1 hour, it was poured into deionized water and quenched to obtain glass fragments. After filtering the glass fragments to remove the water, the mixture was placed in a 10L vertical ball mill. 10kg of 5mm diameter zirconia balls and 2kg of deionized water were added. The mixture was stirred at 250 rpm and ball milled for 4 hours to obtain a glass slurry. The slurry was then sieved and dried to obtain a glass powder with a particle size of 1.5μm to 2μm.
[0051]
[0052] (B) Preparation of organic carrier
[0053] The raw materials were mixed according to the mass ratio in Table 2 below to obtain a raw material mixture, which was heated and stirred at 65° C. for 1 h to form an organic carrier.
[0054]
[0055] (C) Preparation of conductive silver paste
[0056] The organic vehicle, glass powder, and silver powder were mixed in a double planetary mixer according to the mass ratios in Tables 3 and 4, and then three-roll milled for 6 to 8 times. The conductive silver paste was filtered through a 400-mesh cloth to obtain the conductive silver paste. The formula and test results of the conductive silver paste are shown in Tables 3 and 4 below:
[0057]
[0058]
[0059] (D) Preparation of battery cells
[0060] The conductive silver paste prepared above was printed on four secondary grids of a solar silicon wafer at a printing speed of 450 mm / s and a printing pressure of 50 N. The one main grid, two back sub-grids and three main grids used in the test all used conductive silver paste verified by Hongxing Paste. The process was then dried, sintered once and light injected, with a sintering time of 1.5 s and a peak temperature of 760°C. LECO sintering was then performed, with a LECO sintering time of 0.8 s, to form an N-type TOPCon solar cell.
[0061] (E) Cell Measurement
[0062] The above-mentioned N-type TOPCon solar cell was subjected to EL and IV testing. The photoelectric conversion efficiency, opening voltage, filling and short-circuit current data are shown in Table 3 and Table 4. The preferred embodiment 27 cell was used to observe the silver-silicon interface through TESCAN FIB-SEM. Figure 1 , it can be seen that silver and silicon have good contact; after TESCAN xenon plasma milling, the silver-silicon interface is observed using FIB-SEM, and it is seen Figure 2 , it can be seen that there is a shallow transition layer at the silver-silicon interface, which can achieve good contact, reduce ohmic resistance, and achieve high photoelectric conversion efficiency; the glass transition temperature of Example 27 is 427°C, as shown in FIG. Figure 3 shown.
[0063] Figure 1 and Figure 2 The explanations of the English abbreviations are as follows:
[0064] Mag is the abbreviation of Magnification, which refers to the magnification;
[0065] 5.00 kx means the magnification is 5000 times, kx is the magnification;
[0066] 30.0 kx means the magnification is 30,000 times, and kx is the magnification;
[0067] Fov is the abbreviation of Field of View, which refers to the field of view angle;
[0068] WD is the abbreviation of Working Distance, which refers to working distance;
[0069] mm refers to millimeters;
[0070] μm refers to micrometer;
[0071] nm, refers to nanometers;
[0072] Speed refers to the scanning speed;
[0073] DET is the abbreviation of Detector, which refers to detector;
[0074] SE, refers to secondary electrons outside the telescope;
[0075] In-Beam SE, refers to the secondary electrons in the beam;
[0076] Scan Mode refers to the scanning mode;
[0077] ANALYSIS, refers to the general analysis mode;
[0078] UH-RESOLUTION, refers to high-resolution analysis mode;
[0079] Energy, refers to energy;
[0080] keV is the abbreviation of Kiloelectronvolt, which refers to kiloelectron volt.
[0081] Figure 3 The explanations of the Chinese and English abbreviations are as follows:
[0082] DSC is the abbreviation of Differential Scanning Calorimetry, which refers to differential scanning calorimetry;
[0083] mW / mg, mW is the abbreviation of milliwatt, mg is the abbreviation of milligram, and this unit represents the power per milligram of substance;
[0084] Flow refers to flow;
[0085] In ml / min, ml is the abbreviation of milliliter and min is the abbreviation of minute. This unit represents the number of milliliters of fluid flowing through per minute.
[0086] Glass Transition refers to the glass transition temperature;
[0087] Onset refers to the starting point;
[0088] Mid, refers to the midpoint;
[0089] Inflection refers to the inflection point;
[0090] End, refers to the end point;
[0091] Delta CP*, which refers to the change in specific heat;
[0092] TR in 1-TR refers to correction;
[0093] exo, which refers to the release of heat;
[0094] Temperature refers to temperature.
[0095] (F) Acetic acid vapor resistance test
[0096] Based on the results in Tables 3 and 4, Example 27, a preferred embodiment of the present invention, was selected for acetic acid vapor resistance testing. The IV test results are shown in Table 5. After the acetic acid vapor resistance test, the photoelectric conversion efficiency decay rate was 11.9%, which is within the industry standard of 20%, meeting the requirements for N-type TOPCon solar cells.
[0097] The preparation process of acetic acid solution during the acetic acid vapor resistance test is as follows:
[0098] To measure potassium chloride: Place the beaker on an electronic balance and remove the tares to zero, then take 115g of potassium chloride and pour it into the beaker. To measure pure water: Pour the prepared pure water into a measuring cylinder and take 194mL of water into the beaker. To measure acetic acid: Place a rubber dropper vertically into the acetic acid bottle and take 6mL of water and pour it into the beaker. To prepare the liquid: Stir with a glass rod for more than 2 minutes.
[0099] Table 5 Test data before and after acetic acid vapor resistance test
[0100]
[0101] Example 38
[0102] In this embodiment, the heating temperature during the preparation of the organic carrier is 68° C., the heating time is 1.5 h, and the remaining parts are the same as those in the above embodiment.
[0103] Example 39
[0104] In this embodiment, the heating temperature during the preparation of the organic carrier is 65° C., the heating time is 2 h, and the remaining parts are the same as those in the above embodiment.
[0105] Example 40
[0106] In this embodiment, the heating temperature during the preparation of the organic carrier is 70° C., the heating time is 1 hour, and the remaining parts not involved are the same as those in the above embodiment.
[0107] Example 41
[0108] In this embodiment, the conductive silver paste prepared above is printed on four secondary grids of a solar silicon wafer at a printing speed of 400 mm / s and a printing pressure of 50 N. The one main grid, two back sub-grids and three main grids used in the test all use the conductive silver paste verified by Hongxing Paste. Then, drying, one sintering and light injection are carried out. The one sintering time is 1.0 s and the peak temperature is 740 ° C. Then LECO sintering is carried out. The LECO sintering time is 0.7 s to form an N-type TOPCon solar cell.
[0109] Example 42
[0110] In this embodiment, the conductive silver paste prepared above is printed on four secondary grids of a solar silicon wafer at a printing speed of 500 mm / s and a printing pressure of 50 N. The one main grid, two back sub-grids and three main grids used in the test all use the conductive silver paste verified by Hongxing Paste. Then, drying, one sintering and light injection are carried out. The one sintering time is 1.2 s and the peak temperature is 780 ° C. LECO sintering is then carried out. The LECO sintering time is 0.9 s to form an N-type TOPCon solar cell.
[0111] Example 43
[0112] In this embodiment, the conductive silver paste prepared above is printed on four secondary grids of a solar silicon wafer at a printing speed of 480 mm / s and a printing pressure of 50 N. The one main grid, two back sub-grids and three main grids used in the test all use the conductive silver paste verified by Hongxing Paste. Then, drying, one sintering and light injection are carried out. The one sintering time is 1.3 s and the peak temperature is 750 ° C. Then LECO sintering is carried out. The LECO sintering time is 0.8 s to form an N-type TOPCon solar cell.
[0113] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A conductive silver paste, characterized in that: The raw materials of the conductive silver paste include, by mass fraction, 88.2% to 89.0% of silver powder, 1.5% to 2.3% of glass powder and 9.5% of an organic carrier; The glass powder is composed of 57.5% to 59.5% lead oxide, 19.8% to 23% boron trioxide, 7.4% to 9.4% silicon dioxide, 1.8% to 6% aluminum trioxide, 1% to 3% zinc oxide, 1% to 4% diammonium hydrogen phosphate, 0.6% to 3.8% sodium carbonate and 1.7% to 2.3% lithium carbonate, by mass fraction. The organic carrier is composed of an organic carrier A, an organic carrier B and an organic carrier C; The organic carrier A is composed of acrylic resin, hexadecyl alcohol ester and butyl carbitol acetate; The organic carrier B is composed of ethyl cellulose, polyvinyl butyral, butyl carbitol acetate, alcohol ester hexadecene and dimethyl adipate; The organic carrier C is composed of formamidine sulfinic acid, polyamide wax, butyl carbitol acetate, alcohol ester hexadecene and dimethyl adipate; The conductive silver paste is used to prepare four sub-grids of N-type TOPCon solar cells through LECO sintering; In terms of mass fraction, in the 9.5% organic carrier, the content of organic carrier A is 4% to 6.4%, the content of organic carrier B is 3% to 5.4%, and the content of organic carrier C is 0.1%; The organic carrier A is composed of 17% to 23% acrylic resin, 35% to 46.7% hexadecyl alcohol ester and 33.7% to 45% butyl carbitol acetate by mass fraction; The composition of the organic carrier B is as follows: 4.3% to 5.8% of ethyl cellulose, 12.8% to 17.3% of polyvinyl butyral, 62.6% to 70% of butyl carbitol acetate, 5.3% to 10.7% of hexadecyl alcohol ester and 4.7% to 9.3% of dimethyl adipate, based on mass fraction. In terms of mass fraction, the organic carrier C comprises: 7% to 13% of formamidine sulfinic acid, 9.7% to 10.3% of polyamide wax, 19.3% to 20.7% of butyl carbitol acetate, 33.8% to 36.2% of hexadecyl alcohol ester and 24.2% to 25.8% of dimethyl adipate.
2. A method for preparing a conductive silver paste as claimed in claim 1, characterized in that: include: The organic carrier, glass powder and silver powder are stirred and mixed, and then ground and filtered to obtain a conductive silver paste; The preparation process of the glass powder is as follows: lead oxide, boron trioxide, silicon dioxide, aluminum trioxide, zinc oxide, diammonium hydrogen phosphate, potassium carbonate, sodium carbonate and lithium carbonate are mixed and melted, and then quenched to obtain glass fragments, the glass fragments are ball-milled to obtain glass slurry, and the glass slurry is sieved and dried to obtain glass powder; The preparation process of the organic carrier is as follows: preparing an organic carrier A, an organic carrier B and an organic carrier C by mixing and stirring respectively, and obtaining an organic carrier by mixing and stirring the three organic carriers and heating them.
3. The method for preparing the conductive silver paste according to claim 2, characterized in that: The heating temperature after the three organic carriers are mixed is 60°C~70°C, and the stirring time is 1h~2h.
4. An N-type TOPCon solar cell, characterized in that: The four sub-grids of the N-type TOPCon solar cell are prepared by the conductive silver paste described in claim 1, and the preparation process is: printing the conductive silver paste on the four sub-grid positions of the solar silicon wafer, first performing a sintering after printing, and then performing LECO sintering after the first sintering, and finally obtaining the N-type TOPCon solar cell.
5. An N-type TOPCon solar cell according to claim 4, characterized in that: The printing speed is 400mm / s~500mm / s.
6. The N-type TOPCon solar cell according to claim 4, characterized in that: The primary sintering temperature is 740℃~780℃, and the primary sintering time is 1.0s~1.5s; The sintering time of LECO is 0.7s~0.9s.
